Perinatal outcomes following bariatric surgery between a first and second pregnancy: a population data linkage study. (20th November 2019) - Ibiebele, I; Gallimore, F; Schnitzler, M; Torvaldsen, S; Ford, JB
Abstract : Objectives: To describe the population of women having bariatric surgery and compare the pregnancy outcomes for women having bariatric surgery with a non‐bariatric surgery population having a first and second pregnancy. Design: Population‐based record linkage study. Setting: New South Wales (NSW), Australia. Population: All women aged 15–45 years with a hospital record in NSW (2002–2014) and all women giving birth in NSW (1994–2015; n = 1 606 737 women). Methods: Pregnancy and birth outcomes were compared between first and second pregnancies using repeated‐measures logistic regression and paired Student's t ‐tests. Bariatric and non‐bariatric groups were also compared. Main outcome measures: Maternal diabetes, preterm birth (<37 weeks of gestation) and large for gestational age. Results: There was a 13‐fold increase in hospitalisations for primary bariatric surgery during 2002–2014. Compared with the general birthing population, women who had bariatric surgery experienced higher rates of hypertension, diabetes, and preterm birth. Among women who had bariatric surgery between a first and second pregnancy, there were reduced rates of hypertension (OR 0.39, 95% CI 0.29–0.53), spontaneous preterm birth (OR 0.37, 95% CI 0.16–0.86), infants that were large for gestational age (OR 0.63, 95% CI 0.44–0.88), and the admission of infants to a special care nursery or neonatal intensive care (OR 0.64, 95% CI 0.46–0.90) in the second pregnancy. Rates for small‐for‐gestational age and gestational diabetes following surgery were 8.3 and 11.4%, respectively Conclusions: Bariatric surgery between a first and second pregnancy was associated with reductions in obesity‐related adverse pregnancy outcomes. Bariatric surgery performed for the management of obesity in accordance with current clinical criteria is associated with improved pregnancy outcomes in a subsequent pregnancy. Tweetable abstract: Bariatric surgery for obesity may improve pregnancy and birth outcomes in a subsequent pregnancy. Tweetable abstract: Bariatric surgery for obesity may improve pregnancy and birth outcomes in a subsequent pregnancy.